2019
DOI: 10.1103/physrevx.9.011004
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Measurement of an Artificial Atom Embedded in a Parametric Amplifier

Abstract: A crucial limit to measurement efficiencies of superconducting circuits comes from losses involved when coupling to an external quantum amplifier. Here, we realize a device circumventing this problem by directly embedding a two-level artificial atom, comprised of a transmon qubit, within a flux-pumped Josephson parametric amplifier. Surprisingly, this configuration is able to enhance dispersive measurement without exposing the qubit to appreciable excess backaction. This is accomplished by engineering the circ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 45 publications
(48 reference statements)
0
35
0
2
Order By: Relevance
“…In this case, the matrix Ω becomes an overall constant in the non-Hermtian Hamil-tonianĤ tb and can be ignored, and our mapping shows that the dynamics is equivalent to a simple two-mode NDPA in Eq. (38). We stress that this is a distinct mapping from that in Sec.…”
Section: A Standard Non-hermitian Pt -Symmetric Tight-binding Chainmentioning
confidence: 68%
See 1 more Smart Citation
“…In this case, the matrix Ω becomes an overall constant in the non-Hermtian Hamil-tonianĤ tb and can be ignored, and our mapping shows that the dynamics is equivalent to a simple two-mode NDPA in Eq. (38). We stress that this is a distinct mapping from that in Sec.…”
Section: A Standard Non-hermitian Pt -Symmetric Tight-binding Chainmentioning
confidence: 68%
“…Note that the perturbation is now a standard dispersive coupling, something that arises in many measurement contexts. In the case where corresponds to the state of a qubit, this exact setup was realized in a recent superconducting quantum circuit experiment (though operated in a different regime) [38].…”
Section: A Exceptional Point Sensingmentioning
confidence: 99%
“…Furthermore, in [43][44][45] it is shown that, in conjunction with continuous measurement, arbitrarily high levels of squeezing can be achieved in principle. This proposal is closely analogous to a recent experiment in circuit QED has used parametric drive of a microwave cavity to improve the effective efficiency of measurements on transmon qubits [46]. Importantly for quantum state tomography, parametric amplification adds no noise, in principle, and is therefore very effective at transducing small signals.…”
Section: Introductionmentioning
confidence: 80%
“…The parameter choice is γ + =0.05γ − . 10 A straightforward way to verify this is to formulate the constraint equations in terms of the Bloch vectors (rather than the state vectors of equation (4)) then, due to the symmetry of the system, choose say v 1 =0. By inspection, this will lead to v 2 =v 3 =0 also.…”
Section: Wigner Invariance Of mentioning
confidence: 99%
“…Questions of this type [1] may offer novel insights into the nature of open quantum system dynamics and the quantum-classical epistemic distinction [2][3][4]. The observation of single quantum trajectories has now been realised in the laboratory [5][6][7][8][9], with ever increasing detection efficiencies [10]. Additionally, there is strong theoretical evidence for the stability of the particular class of quantum trajectories under consideration [11].…”
Section: Introductionmentioning
confidence: 99%